Wealth transfer taxation - Cremer, Helmuth,Pestieau, Pierre (Univ., Center for Economic Studies [u.a.], 2003)
The purpose of this paper is to survey the theoretical literature on wealth transfer taxation. The focus is normative: we are looking at the design of an optimal tax structure from the standpoint of both equity and efficiency. The gist of this survey is that the optimal design closely depends on the assumed bequest motives. Alternative bequest motives are thus analyzed either in isolation or combined.
Internetausg.: http://www.cesifo.de/pls/ifo_app/DocLinkCESifoDl?getDoc=cesifo1_wp1061.pdf
Keywords: Arbeitspapier; Graue Literatur; Übersichtsarbeit; Erbschaftsteuer; Optimale Besteuerung; Theorie